2012
DOI: 10.1007/s13238-012-2078-6
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming barriers to the clinical utilization of iPSCs: reprogramming efficiency, safety and quality

Abstract: Differentiated cells can be reprogrammed into pluripotent stem cells, known as "induced pluripotent stem cells" (iPSCs), through the overexpression of defined transcription factors. The creation of iPSC lines has opened new avenues for patient-specific cell replacement therapies for regenerative medicine. However, the clinical utilization of iPSCs is largely impeded by two limitations. The first limitation is the low efficiency of iPSCs generation from differentiated cells. The second limitation is that many i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 88 publications
(122 reference statements)
0
15
0
Order By: Relevance
“…These results shed light on the mechanisms governing cell reprogramming, but do not allow transcending the limitations to iPSC clinical translation. Additionally, evidence supporting variability in efficiency of reprogramming and in properties of iPSCs in accordance with the cell type from which iPSCs were generated was also reported . Adult dermal fibroblast has been the first human cell successfully reprogrammed to iPSCs, and, to date, it is still the most used human cell for reprogramming.…”
Section: Introductionmentioning
confidence: 93%
“…These results shed light on the mechanisms governing cell reprogramming, but do not allow transcending the limitations to iPSC clinical translation. Additionally, evidence supporting variability in efficiency of reprogramming and in properties of iPSCs in accordance with the cell type from which iPSCs were generated was also reported . Adult dermal fibroblast has been the first human cell successfully reprogrammed to iPSCs, and, to date, it is still the most used human cell for reprogramming.…”
Section: Introductionmentioning
confidence: 93%
“…Reprogramming efficiency can be enhanced by the inclusion of various factors in addition to those transcription factors responsible for pluripotency. These alternative factors either safeguard the pluripotency of ESCs or play more specific roles in facilitating the reprogramming process but do not maintain pluripotency after it is established 11 . In this study, we found that Rab32 was able to facilitate reprogramming efficiency by regulating lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of different iPSC lines is variable, and this determines their ability to undergo germ-line transmission and live birth following tetraploid complementation 9 10 . Although reprogramming efficiency can be enhanced by the inclusion of other reported factors in addition to pluripotency-related transcription factors, additional factors that play more specific roles in facilitating the reprogramming process remain to be uncovered 11 12 .…”
mentioning
confidence: 99%
“…Despite numerous studies underlying the pathophysiological mechanism of ASD using iPSCs, several concerns should be addressed before iPSC research [ 155 , 156 ]. Current advances in iPSC technology have allowed us to successfully derive patient-specific iPSCs regardless of their reprogramming methods.…”
Section: Discussionmentioning
confidence: 99%